2021
DOI: 10.3390/agronomy11122405
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Assessment and Meteorological Determinants of Atmospheric Drought in Agricultural Areas of East-Central Poland

Abstract: Atmospheric drought is an extremely important issue on a global, regional and local scale, especially in the context of climate change. The aim of the study was to assess the spatiotemporal variation of atmospheric (meteorological) drought in agricultural areas of east-central Poland, represented by the Lublin Voivodeship (Lublin region) in 1971–2015. Average monthly air temperatures and monthly precipitation totals recorded over the 45-year period at 25 weather stations were used in the study. The assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…Based on the values of the Mann-Kendall trends (Z) and the Sen's estimator, our research found a significant positive trend of precipitation totals in the following months: January, February, March, and May -observed only at the station in Włodawa (Table 2). The significant positive trends of precipitation totals in the period of January-March in central-eastern Poland in 1971-2015 are confirmed by the studies conducted by Bartoszek et al (2021). Furthermore, Marosz et al (2011) proved that during the winter the area distinguished by a decrease in precipitation totals was mainly limited to the south-eastern part of the country.…”
Section: Atmospheric Precipitation In the North-easternmentioning
confidence: 78%
See 4 more Smart Citations
“…Based on the values of the Mann-Kendall trends (Z) and the Sen's estimator, our research found a significant positive trend of precipitation totals in the following months: January, February, March, and May -observed only at the station in Włodawa (Table 2). The significant positive trends of precipitation totals in the period of January-March in central-eastern Poland in 1971-2015 are confirmed by the studies conducted by Bartoszek et al (2021). Furthermore, Marosz et al (2011) proved that during the winter the area distinguished by a decrease in precipitation totals was mainly limited to the south-eastern part of the country.…”
Section: Atmospheric Precipitation In the North-easternmentioning
confidence: 78%
“…In the case of Poland, an increase in average annual air temperatures, both in the entire country and in individual physico-geographical regions, has been demonstrated in research conducted by many other authors: Wójcik and Miętus (2014); Wypych et al (2017); Bartoszek et al (2021); Ustrnul et al (2021). Furthermore, Marosz et al (2023) proved that in Poland the highest values of positive air temperature anomalies occurred within the last twenty years .…”
Section: Thermal Conditions In the Area Of North-eastern Lublin Regio...mentioning
confidence: 80%
See 3 more Smart Citations